IMPLEMENTASI KEBIJAKAN PENGELOLAAN HUTAN HAK DI KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Mirwan, Mirwan (Katalogis, 2016)
This research aimed: 1. analyzing of private forest management policy implementation in Donggala Regency Central Sulawesi; 2. analyzing problem of private forest management policy implementation in Donggala Regency Central Sulawesi. The research was couducted in Donggala regency, Central Sulawesi Province. The primary data obtained through observation and interviews and focused discussions with the specified informed intentionally (purposively), while to support of other information obtained by scanning the document. Data were analyzed by descriptive qualitative. The results showed that implementation of Private Forest Management Policy of Donggala Regency not going well. This is evidenced by the analysis of the implementation of policies according to the theory of policy implementation Edward III included by four (4) factors: communication, resources, disposition and bureaucratic structure. These four factors are not going well. It is recommended that socialization and intensive coaching and the need to formulate SOP and regional regulations governing private forest management in Donggala.